Applying stress recovery theory: outdoor intervention for dementia agitation reduction in memory care homes - Guinee, Amelie, author (Colorado State University. Libraries, 2024)
This paper serves as a part-literature review, part-explorative analysis on methods, specifically outdoor exposure, that may reduce agitation experienced by dementia patients. Agitation is reportedly the most common symptom displayed by dementia patients in memory care facilities, which puts significant strain on both the patients and caregivers. Yet, interventions to control and reduce this agitation are still relatively unknown. I hope to compare heart rate variability (HRV) metrics on healthy older adults who have spent time in nature, virtual reality, and indoor conditions to determine whether time spent outdoors promotes stress recovery, a paradigm known as the Stress Recovery Theory. I will use these findings on healthy older adults to inform likely patterns in dementia patients living in memory homes. I specifically hope to understand if implementing certain outdoor-driven shifts in spatial, environmental, or technological designs in memory care facilities may further promote reduced agitation.
Outdoors & reduced agitation in dementia
Department of Honors, Colorado State University. Department of Human Dimension of Natural Resources, Colorado State University. Institute for the Built Environment.
Keywords: heart rate variability; memory care; outdoors; dementia; agitation; stress recovery theory